Pengaruh Komunikasi Organisasi, Kerja Tim, dan Komitmen Organisasi Terhadap Efektivitas Kerja Pengurus KONI Kabupaten Pidie Jaya - Asril Asril; Fauzi Fauzi; Mirza Mirza (Singkite Journal, 2026)
This article examines and analyzes work effectiveness by examining the direct and indirect impacts of organizational communication, teamwork, and organizational commitment. It applies qualitative descriptive research methods and statistical analysis using a path analysis model. A survey was conducted on the management of the National Sports Committee (KONI) in Pidie Jaya Regency, using a questionnaire for data collection. The results revealed: (1) There is a causal relationship between organizational communication, teamwork, and organizational commitment, thus directly and indirectly influencing the management's work effectiveness. The direct and indirect effects of organizational communication are 37.97%, teamwork 30.41%, and organizational commitment 41.86%, respectively, on the work effectiveness of the KONI management in Pidie Jaya Regency. (2) The simultaneous application of organizational communication, teamwork, and organizational commitment significantly contributes to the management's work effectiveness by 37.8%.